Improving the reading comprehension skills of fourth grade MI students through the Know-Want to Know-Learned (KWL) strategy assisted by series picture media - Awaliah, Anisa Nur; Carlian, Yayan; Mahmud, Muhammad Rifqi (Mitra PGMI: Jurnal Kependidikan MI, 2025)
The preliminary reading comprehension test revealed that 25 students scored below the Minimum Completion Criteria (KKM), while 3 students scored above it, with an average score of 51.15. This study aims to improve students’ reading comprehension using the Know-Want to Know-Learned (KWL) strategy, supported by series image media. A quasi-experimental design with a Nonequivalent Control Group was used, consisting of three groups: the first experimental group using KWL with series image media, the second experimental group using KWL, and the control group applying conventional methods. The ANOVA test showed a significant difference with a p-value of 0.004 (p < 0.05). The average posttest scores were 83.00 for the first experimental class, 80.47 for the second experimental class, and 74.30 for the control class. The n-gain scores indicated high categories for both experimental classes (0.78 and 0.75) and a medium category for the control class (0.68). These results suggest that the KWL strategy significantly enhances students’ reading comprehension.